"Western" Influence on Some Palace Gardens in Historical Peninsula of Istanbul. Issue 4 (1st December 2018) - Bekar, M.; Var, M
Abstract : From past to present, Istanbul has witnessed many empires and historical events. This accumulation has made Istanbul one of the most important cities in Turkey. The architecture and historic potential of the city dates back to centuries ago. Palace architecture is the most important cultural inventories of the city. Over time, technological developments and the industrial revolution brought the "western influence" to Turkey. This effect is observed on planning character and on the planting design. The main material of the work is Topkapı Palace, Beylerbeyi Palace and Dolmabahçe Palace. In this context, this paper consist of three stages. Literature studies have been carried out in the first stage. "Western effect" on the palaces has been investigated after the second step consisting of the field study and mapping. As result of the examinations, western influence was studied in three stages as general planning character, structural material and plant material. As a result of the study, results were obtained for each title. Suggestions were made for rehabilitation and palace gardens planning.